2015
DOI: 10.1007/s13277-015-3328-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs POLR2E rs3787016 C/T and HULC rs7763881 A/C polymorphisms are associated with decreased risk of esophageal cancer

Abstract: Worldwide, rates of esophageal cancer have been keeping highly in recent decades. Genetic variants in multiple cellular pathways might play an important role in altering risk of esophageal carcinoma. In this study, long noncoding RNAs (lncRNAs) functional single nucleotide polymorphisms (SNPs) were investigated in Chinese Han populations. We have genotyped the ANRIL rs2151280 T/C, POLR2E rs3787016 C/T, and HULC rs7763881 A/C SNPs in 380 esophageal squamous cell carcinoma (ESCC) cases and 380 cancer-free contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Recent research focusing on lncRNAs has improved our understanding of the complex regulatory mechanisms underlying tumorigenesis and metastasis in human cancers [10]. In ESCC, the dysregulation of some lncRNAs, such as MALAT1 [23,24], 91H [25], HOTAIR [26], ANRIL [27,28], and MEG3 [29,30], promotes or inhibits the progression and metastasis of tumors and is closely associated with poor survival [31]. These results confirm that lncRNAs are potential diagnostic and therapeutic biomarkers in ESCC.…”
Section: Discussionmentioning
confidence: 75%
“…Recent research focusing on lncRNAs has improved our understanding of the complex regulatory mechanisms underlying tumorigenesis and metastasis in human cancers [10]. In ESCC, the dysregulation of some lncRNAs, such as MALAT1 [23,24], 91H [25], HOTAIR [26], ANRIL [27,28], and MEG3 [29,30], promotes or inhibits the progression and metastasis of tumors and is closely associated with poor survival [31]. These results confirm that lncRNAs are potential diagnostic and therapeutic biomarkers in ESCC.…”
Section: Discussionmentioning
confidence: 75%
“…Jin et al firstly reported the rs3787016 in POLR2E gene that was associated with prostate cancer susceptibility based on prostate cancer genome wide association study [7]. Subsequently, authors investigated the role of rs3787016 in esophageal cancer [33] and prostate cancer [8, 34]. Meta-analysis results revealed that rs3787016 can predict the cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, Li et al did not find the significant risk for rs1016343, and find that PRNCR1 rs13252298, rs7007694, rs1456315 polymorphisms were associated with gastric cancer risk [22]. Additionally, lncRNA H19 [2732] and POLR2E [7, 8, 33, 34] polymorphisms were studied widely. The published results of H19 and POLR2E polymorphisms with cancer risk were also conflicted.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that the rs3787016 TT genotype was a risk factor for female BC in a Chinese population. In contrast, a case-control study of ESCC demonstrated that POLR2E rs3787016 CT or CT/TT genotype had a decreased risk of ESCC 25. The different findings in the above studies might be explained as follow.…”
Section: Discussionmentioning
confidence: 84%